“I DO NOT TRUST THESE ORGANIZATIONS!” WHYUNIVERSITY STUDENTS DO NOT VOLUNTEER IN TURKEY - (:unkn) unknown (My University, 2019)
Why some people do not volunteer? After doing a comprehensive literature review, wesummarized all potential reasons that have been mentioned so far. However, we alsofound important discrepancies between different studies. Thus, we concluded that anexploratory research can be useful to understand why some people do not volunteer.In this study, by conducting nine focus groups we analyzed why university studentsfrom various disciplines of social sciences do not volunteer in Turkey. Focus groupswere realized with 52 university students in Istanbul. Results revealed that the primaryreason for the reluctance of university students to volunteer was related to trust issues.In other words, in Turkey, university students do not volunteer as they do not trustNGOs. Some other important reasons were also discussed in the article.

Bu çalışmada yanıt aranan temel soru, bazı insanların neden gönüllü olmadıklarıdır. Gönüllülük yazınında bu konuya değinen kuramsal ve görgül çalışmalara ilişkin kapsamlı bir yazın taraması bize ilgili yazındaki çalışmaların bulgularının birbirleriyle çeliştiğini göstermiştir. Bu nedenle, keşifsel ve görgül bir çalışmanın faydalı olacağı düşünülmüştür. Bu bağlamda, 9 odak grup çalışmasında toplamda 52 üniversite öğrencisi ile odak grup görüşmeleri yapılarak İstanbul’da eğitim gören üniversite öğrencilerinin neden STK’larda gönüllü olmadıkları anlaşılmaya çalışılmıştır. Sonuçlar, öğrencilerin STK’lara gönüllü olarak katılım göstermemesinin temel nedeninin bu kurumlara duyulan güvensizlikle ilgili olduğunu göstermiştir. Öğrencilerin STK’lara gönüllü olarak katılımının önündeki diğer engeller de araştırma bulguları içinde sunulmuş ve tartışılmıştır. Anahtar Kelimeler: gönüllülük, gönüllü
“BU ORGANİZASYONLARA GÜVENMİYORUM!” TÜRKİYE’DE ÜNİVERSİTE ÖĞRENCİLERİNİN STK'LARDA GÖNÜLLÜ OLMAMA NEDENLERİ